Coke-resistant Y2O3-promoted cobalt supported on mesoporous alumina for enhanced hydrogen production - Mahadi, Bahari; Setiabudi, H. D.; Nishino, Tomomichi; Ayas, Nezihe; Vo, Dai-Viet N. (Elsevier Ltd., 2021)
In this work, the δ%Y–10%Co/MA (δ = 0, 1, 2, 3, and 5 wt%) catalysts synthesised by sequential incipient wetness impregnation were characterised and evaluated in CH4 dry reforming. Superior catalytic performances were shown by 3 wt% Y2O3 loading (CH4 conversion = 85.8%, and CO2 conversion = 90.5%), followed by 2 wt% > 5 wt% > 1 wt% > 0 wt% Y2O3 loading. This result was attributed to the favorable catalytic properties of 3 wt%Y–10%Co/MA including small Co particle size, high Co dispersion, high amount of atomic ratio (Co/Al), and high number of lattice oxygen vacancies. The excess Y2O3 addition (>3 wt%) led to inevitably blocked Co active sites and resulted in decreasing catalytic performance. The 3 wt% Y2O3 promoter loading recorded the lowest carbon deposited (7.0%) due to the highest oxygen vacancies (78.1%) compared to 1, 2 and 5 wt% Y2O3.